Abutment Screw Loosening in Single Implant Restorations: Evaluation of Fracture Strength of Implant-Supported Cement-Retained Monolithic Zirconia Restorations Repaired with Porcelain and Composite Resin - Hamid Neshandar Asli (Wolters Kluwer Medknow Publications, 2021)
Aim: To assess the fracture strength of repaired implant-supported cement-retained monolithic zirconia restorations with porcelain and composite resin. Materials and methods: Nighty monolithic zirconia crowns were cemented over the implant abutments, and divided into three groups (n = 30): control, screw access hole preparation in the crown and its restoration with composite resin (HC), and screw access hole preparation in the crown and its restoration with feldspathic porcelain (HP). Fracture strength was measured by a universal testing machine. Data were analyzed (α < 0.05). Results: The maximum fracture strength was in the control group (764.23 ± 108.41 N), whereas the minimum was in HC group (686.25 ± 101.86 N). The mean fracture strength in HC group was significantly lower than that in the control group (P = 0.008). No significant difference was noted between other groups (P > 0.05). Conclusion: Repaired implant-supported monolithic zirconia crowns with feldspathic porcelain provided a fracture strength comparable to that in the control group.